A longitudinal study of developmental quotients in early interventions for children with intellectual disability - Cai, Shaocheng; Wen, Yu; Zhan, Yingjie; Yuan, Liuliang (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to examine the longitudinal relationships among different developmental quotients (DQs) in children with intellectual disability, focusing on the temporal dynamics of adaptive, language, and personal-social development over a two-year period, thereby informing more targeted early intervention strategies.MethodsWe retrospectively analyzed data from 94 children (72 males, 22 females, aged 2–5 years) diagnosed with intellectual disability who had continuously received behavioral interventions for neurodevelopmental disorders at our hospital over a two-year period. The dataset included demographic information and DQs for adaptive behavior, language ability, and personal-social skills, which were assessed using the Chinese version of Gesell Developmental Scale. Cross-lagged panel modeling was conducted using Mplus 8.3 to examine the correlations among DQ domains at the same time point, their stability across time, and cross-domain predictive relationships.ResultsThe reciprocal associations model, which incorporated cross-lagged paths to the stability model, demonstrated good fit. At all time points, adaptive, language, and personal-social DQs were moderately to strongly correlated. Each domain showed high temporal stability, as indicated by significant autoregressive paths. Adaptive DQ at Time 1 and Time 2 significantly predicted language and personal-social DQs at subsequent time points (β = 0.272–0.337, p < 0.01). Additionally, language DQ at Time 1 predicted personal-social DQ at Time 2. In contrast, neither language nor personal-social DQ predicted future adaptive DQ.ConclusionAdaptive functioning is prospectively associated with later development of language and personal-social skills in children with intellectual disability. Early interventions that prioritize adaptive skill development may yield broader benefits across other developmental domains. Further research is warranted to develop and evaluate intervention models that strategically leverage these directional relationships to optimize long-term outcomes.